2022
DOI: 10.3389/fpsyg.2022.978572
|View full text |Cite
|
Sign up to set email alerts
|

The psychometric properties of the Persian version of the moral injury symptoms scale-health care professionals version

Abstract: BackgroundHealth care professionals face a number of problems during crises, such as the COVID-19. Studies addressed the prevalence of moral injury among healthcare professionals during the COVID-19 outbreak. Lack of a valid standard of moral injury among health care professionals is one of the factors that has made it difficult to identify and treat this complication. This study aimed to evaluate the psychometric properties of the Moral Injury Symptoms Scale-Health Care Professionals (MISS-HP) among health ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The PRISMA flowchart delineates the review process (see figure 1). Of the 81 full texts included in the review,6 12–21 43–112 some reported multiple studies in the same paper, so there were 88 separate studies included in the review. Of these, six reported prevalence estimates or average scores that could not be pooled, so they were included in the narrative synthesis only.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The PRISMA flowchart delineates the review process (see figure 1). Of the 81 full texts included in the review,6 12–21 43–112 some reported multiple studies in the same paper, so there were 88 separate studies included in the review. Of these, six reported prevalence estimates or average scores that could not be pooled, so they were included in the narrative synthesis only.…”
Section: Resultsmentioning
confidence: 99%
“…The number of items and scoring is based on the typical use of the scale.*Some papers modified the Likert scale and used a cut-off of 3+ ‘sometimes’ and 4+ ‘often’51 or 3+ ‘agree’ 70 90†The German MISS-HP (G-MISS-HP) uses a 9 item scale with a cut-off>28.5,107 The Persian MISS-HP uses a cut-off>36.5 92‡PMIE questions precede the MIOS symptoms scale and can be quantified as endorsed (yes/no).AoW, Atrocities of War; BMIS, Brief Moral Injury Screen; EMIS-M, Expressions of Moral Injury Scale-Military Version; EMIS-SF, Expressions of Moral Injury Scale-Short Form; LFB, Leadership Failure or Betrayal; MIA-PSP, Moral Injury Assessment for Public Safety Personnel; MIES, Moral Injury Events Scale; MIOS, Moral Injury Outcome Scale; MIQ-M, Moral Injury Questionnaire—Military version; MIQ-T, Moral Injury Questionnaire—Teacher version; MISS-HP, Moral Injury Symptoms Scale—Health Professionals; PCoW, Psychological consequences of War; PTED, post-traumatic embitterment disorder.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The factor loadings, representing how well each item correlates with its underlying dimension, demonstrated strong convergent validity (CR values >0.7). Convergent validity, confirmed by high CR values and significant eigenvalues (indicating the variance captured by a factor), ensures that the dimensions accurately reflect the constructs they are intended to measure ( 41 , 42 ). Our factor analysis led to the removal of certain items, a decision aimed at enhancing the HIPQ’s construct clarity.…”
Section: Discussionmentioning
confidence: 96%